Toll-Like Receptors Signaling Contributes to Immunopathogenesis of HBV Infection - Yasuteru Kondo; Yoshiyuki Ueno; Tooru Shimosegawa (Gastroenterology Research and Practice)
Innate and adaptive immune systems have important role in the pathogenesis of acute and chronic infection with hepatitis B virus (HBV). These immune responses are mediated through complex interactions between the innate immune response and adaptive immune response. Toll-like receptors (TLRs) are a family of innate immune-recognition receptors that recognize the molecular patterns associated with microbial pathogens. So far, TLR1 to 13 were found in human or mice and investigated to detect the target molecules and the downstream mechanisms of these unique systems. Stimulation by their ligands initiates the activation of complex networks of intracellular signaling transduction and innate and adaptive immune-related cells (NK, NK-T, monocytes, dendritic cells, T cells, B cells, and Tregs, etc.). However, reports on such relationships between HBV and TLRs have been relatively rare in comparison to those on HCV and TLRs, but have recently been increasing. Thus, a review of TLRs involved in the pathogenesis of HBV infection may be needed toward better understanding of the immunopathogenesis of HBV infection.